THE EFFECTIVENESS OF e-COMIC MEDIA ON STUDENT LEARNING OUTCOMES TO COMPREHEND JAVANESE STORY TEXTS IN 3RD GRADE - Zakia, Rahma Choliza; Rahutami, Rahutami; Delawanti, Crisyarani Denna (JPSD (Jurnal Pendidikan Sekolah Dasar), 2024)
One way to help preserve the Javanese language is through learning. To preserve the Javanese language, a deeper introduction is necessary so that it can be effectively applied in the surrounding environment. The issue faced is that students find Javanese language learning boring because teachers need to use instructional media that can enhance the quality of Javanese language education. The purpose of this research is to evaluate how effectively e-comic media improves the knowledge of 3rd-grade students in understanding Javanese folktales. This research employs a quasi-experimental and quantitative methodology. The non-equivalent control group design is the type of quasi-experimental approach used. The data collection method utilized is testing. Instrument tests used include validity tests, reliability tests, difficulty level analysis, discriminative power, and distractor function. The prerequisite tests used are normality tests and homogeneity tests. The hypothesis test used is the T-test. According to the data, the experimental class outperformed the control class in terms of improvement. The experimental class achieved an average post-test score of 76.6, while the control class averaged 64.3. The experimental class showed a score increase of 21 points, or 37.77%, whereas the control class improved by 16.27%. These findings support the hypothesis that e-comic media positively affects student learning outcomes. Additionally, the school will adopt this media so it can be adapted to the narratives present in the relevant curriculum.